Geographic context of applying for grants from Norway, Iceland and Liechtenstein and the use grant money in Lithuania in the framework of the 'European economic area (EEA)' and the 'Norway' programmes - Spiriajevas, Eduardas (RUS, 2012)
The article presents a geographic analysis of applying for grants and allocation of funds in the framework of the 'European Economic Area' and 'Norway' programmes in the territory of Lithuania in 2004-2009. Priority sectors of cooperation are identified.